2010
DOI: 10.1136/bjsm.2010.078725.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plyometric exercises on selected motor abilities of university level female basketball players

Abstract: Today there is not a single sport in the world at the competitive level for which resistance training in some or the other form is not used as conditioning exercises. Plyometric training is an excellent method of developing body power and it is proved as a very effective method for improving explosive strength. The purpose of the study was to fi nd out the effects of plyometric exercises on selected motor abilities of university level female basketball players. The subjects, 20 female basketball players of Lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Draganović & Marković (2011); Asadi & Arazi (2012); and Asadi (2013) found that a 6-week plyometric training (2 times per week) for a basketball, junior and senior age sample leads to a significant improvement in the sprint speed of the S20m. Similar results were achieved (Benis, Rossi, Russo, & La Torre, 2015;Chaudhary & Jhajharia, 2010) for a sample of basketball players, that 8-week plyometric training (2 times per week) led to a significant improvement in 20m sprint results. Also, plyometric training in combination with exercises leads to a significant improvement in the speed of the sprint of young basketball players.…”
Section: Discussionsupporting
confidence: 80%
“…Draganović & Marković (2011); Asadi & Arazi (2012); and Asadi (2013) found that a 6-week plyometric training (2 times per week) for a basketball, junior and senior age sample leads to a significant improvement in the sprint speed of the S20m. Similar results were achieved (Benis, Rossi, Russo, & La Torre, 2015;Chaudhary & Jhajharia, 2010) for a sample of basketball players, that 8-week plyometric training (2 times per week) led to a significant improvement in 20m sprint results. Also, plyometric training in combination with exercises leads to a significant improvement in the speed of the sprint of young basketball players.…”
Section: Discussionsupporting
confidence: 80%
“…The smallest number of respondents was in the research Adorable Caparin & Abba (2011) and it amounted to nine participants and the biggest was in the research Bavli (2012) with 91 respondents. In nine of the researches, the respondents were female basketball players (Chang, Hsu, Chen & Lin, 2005;Chaudhary & Jhajharia, 2010 Torre, 2015; Khazai & Hematfar, 2015), kod dva istraži-vanja su bili i muškog i ženskog pola (Bavli, 2012a;Ramachandran & Pradhan, 2014), a kod svih ostalih istraživanja su bili muškog pola. Najmlađi uzorak ispitanika bio je u istraživanju Khazai & Hematfar (2015) i iznosio je od 11 do 12 godina, a najstariji u istraživanju Morsal at al.…”
Section: Resultsmentioning
confidence: 99%
“…Najmanji broj ispitanika bio je u istraživanju Adorable Caparino & Abbu (2011) i iznosio je devet ispitanika, a najveći u istraživanju Bavli (2012)a sa 91. ispitanikom. Kod devet istraživanja ispitanici su bili ženskog pola -košarkašice (Chang, Hsu, Chen & Lin, 2005;Chaudhary & Jhajharia, 2010;Adibpour, Bakht & Behpour, 2012;Komal & Singh, 2013;Zarić, 2014; Attene at al., 2014; McCormick at al., 2015; Benis, Rossi, Russo & La Lesiecki, 2006), are of great importance for success in sports such as basketball (Nedeljković, 2004;Bobbert, 1990), and are manifested in situations such as jump shot and jump towards the ball (Manojlovic & Erčulj, 2013). In men's professional basketball a player has to jump 46 ± 12 times (Castagna, Chaouachi, Rampinini, Chamari & Impellizzeri, 2009), and some authors claim that basketball in the whole match (40min games) takes up to 100 different jumps (Manojlović & Erčulj, 2013).…”
Section: Rezultatimentioning
confidence: 99%
See 1 more Smart Citation